Effect of Public Librairies in the Attainment of Health Millennium Development Goals in Senegal - Sow, Papa Gallo; Vinekar, V. (Intelektual Pustaka Media Utama, 2012)
This study surveys the roles of Public libraries in the attainment of health Millennium Development Goals in Senegal. It also identifies the health-information needs of the community and information services rendered by the libraries. The role of public libraries in the attainment of health-MDGs has been a daunting task for public libraries as a result of government negligence. The methodology adopted for the study is the survey design in which questionnaires was used for obtaining data. The target population was public library staff/users in Senegal. The result showed that public libraries have played significant role towards the attainment of health-MDGs and library users make significant demand for all categories of health information especially in the area of maternal and childcare. However, majority of the public libraries have no Internet services. The findings makes it imperative for all other relevant agencies to key into the health-MDGs especially in assisting the Public Libraries. The study will bring to the awareness of users, the roles public libraries plays in supporting local and international policies and the provision of information services for library users.DOI: http://dx.doi.org/10.11591/ijphs.v1i1.701